S120 Right Ventricular Dysfunction In Pulmonary Hypertension With Combined Pulmonary Fibrosis And Emphysema Syndrome. (10th November 2014) - Swift, AJ; Rajaram, S; Capener, D; Elliot, C; Condliffe, R; Hurdman, J; Kiely, DG; Wild, JM
Abstract : Introduction: Recent studies have suggested that the coexistence of emphysema and fibrosis alters clinical outcome. The aim of this study was to investigate the comparative clinical characteristics, pulmonary function, haemodynamics and right ventricular (RV) function and outcome in patients with pulmonary hypertension associated with combined pulmonary fibrosis and emphysema (PH-CPFE), chronic obstructive pulmonary disease (PH-COPD) and interstitial lung disease (PH-ILD). Methods: In 79, incident patients with pulmonary hypertension associated with respiratory disease, cardiovascular magnetic resonance imaging was performed at 1.5T. Emphysema and fibrosis were scored on high resolution computed tomography scans. Demographic data, lung function tests and right heart catheterisation were also performed. Results: Patients with pulmonary hypertension associated with combined pulmonary fibrosis and emphysema syndrome had lower right ventricular ejection fraction when compared to both patients with PH-COPD and PH –ILD (p < 0.05). At Kaplan-Meier analysis, patients with PH-CPFE patients had significantly worse outcome than those with PH-COPD (p = 0.015), and borderline worse outcome than patients with PH-ILD (p = 0.050), Figure . 48 of 94 patients were diagnosed with severe PH-RESP, defined at mPAP≥40 mmHg. WHO functional class (p = 0.036), TLCO (p = 0.019), RVEF (p = 0.033) were significant independent predictors of outcome in patients with severe PH-RESP. Conclusion: Patients with severe PH-RESP have a dire clinical outcome. RVEF is an independent predictor of adverse outcome in these patients and may be a powerful biomarker for use in clinical trials of targeted therapy in patients with pulmonary hypertension associated with lung disease, particularly given the unreliable performance of echocardiography in patients with advanced lung disease.